2014
DOI: 10.1089/brain.2014.0237
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Integrity, and Function of the Hypoplastic Corpus Callosum in Spina Bifida Myelomeningocele

Abstract: Although there are many studies of people with complete or partial hypogenesis of the corpus callosum (CC), little is understood about the hypoplastic CC in which all structures are present but thinned. Spina bifida myelomeningocele (SBM) is a model organism for such studies because many have either a hypogenetic or hypoplastic CC. We used diffusion tensor tractography (DTT) to evaluate the hypoplastic CC in SBM and its relation to interhemispheric functions and intelligence quotient (IQ). Participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…In support of this hypothesis, we found that people with SBM and both CC hypoplasia and hypogenesis showed decreased FA and AD, and increased RD compared to the TD group. These results are supported by a previous investigation of CC microstructure that was restricted to CC hypoplasia in SBM, which showed reduced FA and increased RD in the entire CC, with posterior subregions showing the greatest reductions in integrity (Crawley et al, 2014).…”
Section: Microstructure and Macrostructuresupporting
confidence: 87%
See 1 more Smart Citation
“…In support of this hypothesis, we found that people with SBM and both CC hypoplasia and hypogenesis showed decreased FA and AD, and increased RD compared to the TD group. These results are supported by a previous investigation of CC microstructure that was restricted to CC hypoplasia in SBM, which showed reduced FA and increased RD in the entire CC, with posterior subregions showing the greatest reductions in integrity (Crawley et al, 2014).…”
Section: Microstructure and Macrostructuresupporting
confidence: 87%
“…Diffusion tensor imaging (DTI) and tractography methods have made it possible to examine the structure of the CC and identify various atypical white matter connections. Crawley et al (2014) used DTI and deterministic tractography to segment the CC in individuals with thinning of the CC due to hydrocephalus in spina bifida and found that posterior sections had the greatest reductions in volume and microstructural integrity. In addition, Probst bundles, which are anomalous, anterior-posterior coursing connections, as well as interhemispheric sigmoid-shaped bundles connecting heterotopic cortical regions, have been identified in individuals with congenital disorders affecting CC development (Barkovich and Raybaud, 2012;Lee et al, 2004;Owen et al, 2013;Tovar-Moll et al, 2007Wahl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies of the corpus callosum show marked volume and integrity differences, especially posteriorly in cases with hypogenesis or severe hypoplasia 49. Reduced integrity has also been shown in the genu, but not in the anterior commissure 50. There is recent evidence that corpus callosal defects can also be associated with closed spinal dysraphism 51.…”
Section: Mechanisms and Pathophysiologymentioning
confidence: 99%
“…The patients were diagnosed late and often as a consequence of urologic symptoms or skin pits. Other studies have reported that hydrocephalus and Chiari II malformation are present in the majority of children with open NTDs , with the occurrence of severe brainstem dysfunction and subsequent need for surgical decompression in 4–8.8% . Cognitive difficulties have been described in children with open NTDs both in regard to low IQ and the need for assistance with schoolwork .…”
Section: Clinical Features According To Diagnosismentioning
confidence: 99%
“…Previous research has pointed to the associated presence of hydrocephalus as an explanation , which is in agreement with our data. There may be an association between reduced cognition and hydrocephalus as a result of anomalies in cortical thickness and gyrification or corpus callosum hypoplasia .…”
Section: Clinical Features According To Diagnosismentioning
confidence: 99%